G459(P) Picu quality improvementproject: Improving compliance with tracheostomy safety strategies. (24th May 2017) - Wakeman, R; Jones, C Davies; Potterton, A; Kelly, A; Abella, F; Combes, J; Chan-Dominy, A; Zizkova, E; Casanueva, L
Abstract : Aims: Tracheostomy can be an infrequent procedure in PICU and has significant associated risks in particular tube occlusion or accidental decannulation. 1 In 2014 the National Tracheostomy Safety Project Paediatric team developed national algorithms for managing common tracheostomy emergencies. These had recently been incorporated into updated tracheostomy guidelines within our institution. A tracheostomy quality improvement (QI) team was set up to embed best practice within daily tracheostomy management. The project aim was to improve tracheostomy safety within PICU by achieving 100% compliance with the display of bedhead forms, emergency algorithms and the contents of the patient's tracheostomy box in the bedspace of all patients with a tracheostomy within 4 months. Method: An inter-professional QI project group was established April 2016 comprising PICU and Children's Long Term Ventilation team staff. The team used Plan Do Study Act (PDSA) cycles to repeatedly evaluate interventions and then refine changes in response. Efficacy was measured and recorded on run charts to track progress (Figures 1 and 2). Results: The initial compliance with tracheostomy emergency contents was 60%–70%. Appropriate bedhead signs and emergency algorithms were not being displayed in the bedspace (0% compliance). In total 25 PDSA cycles were undertaken. The run chart (figure 2) demonstrates a consistent improvement in percentage compliance with required emergency box contents during this phase of the project to 92%). The annotated PDSA cycles refer to the examples of interventions: Tracheostomy safety checklist developed for use at bedside Tracheostomy box contents list aligned to match latest practice recommendations One required item not stocked, therefore made readily available Bedside training and coaching around the differing risks between managing new and established tracheostomies Abstract G459 Figure 1: Compliance with tracheostomy box contents. Figure 2 Emergency algorithm and bedhead sign display Both outcomes demonstrated consistent, sustained improvement during the study period. Conclusion: During early PDSA cycles a number of previously unrecognised contributing factors were identified as preventing compliance with the established project aim. The QI methodology incorporating PDSA cycles allowed rapid changes to clinical practice in response to issues identified. Multiple factors affecting compliance were addressed during the project. Reference: Kremer B et al (2001) 'Indications, complications, and surgical techniques for paediatric tracheostomies—An update' J Ped Surg Vol 37, Issue 11, Pages 1556–1562